Acute Effects of Loaded Half-Squat Jumps on Sprint Running Speed in Track and Field Athletes and Soccer Players. Issue 6 (June 2016) - Vanderka, Marián; Krčmár, Matúš; Longová, Katarína; Walker, Simon
Abstract : Abstract: Vanderka, M, Krčmár, M, Longová, K, and Walker, S. Acute effects of loaded half-squat jumps on sprint running speed in track and field athletes and soccer players. J Strength Cond Res 30(6): 1540–1546, 2016—The purpose of the study was to determine the acute responses to a jump squat protocol designed to induce postactivation potentiation on sprint running performance in experienced track and field athletes and soccer players. Twenty-five regional level athletes (12 track and field: ∼17 years; ∼177 cm; ∼73 kg and 13 soccer: ∼18 years; ∼175 cm; ∼72 kg) performed 2 test sessions assessing 40-m sprint running performance in a balanced, crossover design. Dual-beam light timing gates measured 0–20 and 20–40 m sprint times before and after either 9 minutes of sitting (control) or 2 sets of 6 repetition half-squat jump with the load eliciting maximum power (experimental) conditions. Sprint performance was significantly enhanced over both 0–20 m (3.09 ± 0.07 to 3.04 ± 0.08 seconds; Δ ∼1.5%; p ⩽ 0.05) and 20–40 m (2.42 ± 0.09 to 2.39 ± 0.09 seconds; Δ ∼1%; p ⩽ 0.05) in track and field athletes only. Also, the magnitude of enhanced sprint performance was related to baseline 0–20 m sprint performance ( r = 0.44; p = 0.028; n = 25). It seems that using loaded half-squat jumps to enhance sprint performance could be used in training of high-level young athletes.